Практическое применение разработанного приложения AdjNet в морфологических задачах - Каменева, И. В.; Афанасьев, А. С. (НТУ "ХПИ", 2013)
In the paper reviewed the performance of developed application "AdjNet" based on a common model of Russian inflection of adjectives. It decides the problems of synthesis, analysis and normalization of wordforms, and also analyzes the phonetic of full adjectives in sound form.
Keywords: структуры мозгоподобные; сеть реляционная; модель; морфология; имя прилагательное; язык русский; словоизменение; фонетика